A vortex method of 3D smoke simulation for virtual surgery. (January 2021) - Hu, Lingyan; Chen, Majun; Liu, Peter X.; Xu, Shaoping
Highlights: We proposed 3D-VPICA method aims to simulate smoke and resolve the tension between accurate smoke motion details and a high computational burden. In order to simulate the collision of smoke particles with moving objects with irregular surfaces, the proposed APA algorithm ensures that the impermeable and non-slip boundary conditions are satisfied. The proposed method was tested experimentally via a virtual surgery system. The 3D-VPICA and the APA were applied to simulate the smoke produced by electrical cutting. The results show that the virtual smoke had high fidelity and fluency. Abstract: Background and Objective: A realistic virtual surgery simulation needs to simulate smoke as electrical cutting causes thermal tissue damage. The vortex particle method of simulating smoke can realistically present the vortex details and motion trajectory of the smoke, but there is high computational cost. Methods: To address this problem, we propose the 3D Vortex Particles in Cube Algorithm (3D-VPICA). 3D-VPICA can realistically show the visual effect of smoke and reduce the computational cost. In addition, in order to enhance the reality of the smoke, we propose the Auxiliary Particles Algorithm (APA) method to deal with the collision problem of smoke. Results: The 3D-VPICA can calculate the velocity of the vortex particles speedily with the help of cube grids and with the complexity decreasing from O ( N 2 ) to O ( N ) + O ( M log 2 M ). The APA can ensure that boundary conditions are satisfied when the smoke collides with irregular surfaces. Experimental results show that 3D-VPICA is faster than traditional methods of smoke simulation and that APA is successful in simulating smoke colliding with moving objects with irregular surfaces. Conclusions: The proposed 3D smoke simulation method was applied to a virtual surgery system using a high frequency electric knife. The cutting and coagulate operations were fluent and the smoke flowed with fidelity.